Financing grassroots initiatives in solid waste management: benchmarking the Tanzanian experience against international practices - Mesia Ilomo; Goodluck Charles (Environmental Research Communications)
Although financing solid waste management (SWM) is commonly reported as a critical challenge facing waste management initiatives in most developing countries, few studies have attempted to investigate the options for financing SWM initiatives and the extent to which they are accessible by grassroots actors. To address this knowledge gap, this study explored the models for financing SWM initiatives in Tanzania and benchmarked them against international practices. In addition, the study investigated the advantages and disadvantages of the financing options available for grassroots initiatives. The findings from the systematic literature review and analysis of seven waste collection initiatives indicate that, while in advanced countries SWM activities are financed through carbon financing, and loans from the capital market, financial institutions and international agencies, in Tanzania, they are mostly financed through interest-free municipal loans, user charges (service contract), commercial loans, grants and members’ subscriptions. However, the service contract was the most common financing model in Tanzania, mainly because of the limited budget the government allocated for waste management activities. The financing options identified have some advantages and disadvantages, depending on their cost, flexibility, terms and conditions, accessibility and the inclusiveness of beneficiaries. Accordingly, we propose a hybrid model for financing SWM encompassing the public and private sector, especially in a context where government budgets allocated for SMW are limited.